The effect of traction straight leg raise (TSLR) versus compression straight leg raise (CSLR) on hamstring tightness in collegiate - KUMBHAR, TEJASHREE S; PATIL, SMITA C (International Journal of Psychosocial Rehabilitation, 2020)
To determine the effect of traction straight leg raise (TSLR) versus compression straight leg raise (CSLR) on hamstring tightness in collegiate. An experimental study was done, which included92 subjects. They were selected by simple random sampling method as per the inclusion and exclusion criteria of the study. The inclusion criteria were, Knee extension angle (KEA) greater than 20 degrees where KEA is the degrees of knee flexion from terminal knee extension. The exclusion criteria were,Surgery of hamstring or lumbar muscles in past 6 months, Lower extremities or spine fracture in past 6 months ,Subjects with post-traumatic stiffness of knee and hip joint, Subjects with postoperative conditions lower limb.The study was conducted at physiotherapy OPD of Krishna institute of medical sciences deemed to be university karadfor a duration of 6 months. The ethical clearance for the study was taken from institutional ethical committee of KIMSDU karad. Active knee extension test mean of group A is 29.45 and standard deviation is 12.15. active knee extension test mean of group B is 30.02 and standard deviation is 9.65. p value of active knee extension test is 0.8 and t value is 0.24. Inference is not significant. Straight leg raise test mean of group A is 27.02 and standard deviation is 9.61. straight leg raise test mean of group B is 29.06 and standard deviation is 8.99. p value of straight leg raise is 0.29 and t value is 1.05. Inference is not significant. Finger toe touch test mean of group A is 8.04 and standard deviation is 3.82. finger toe touch test mean of group B is 6.26 and standard deviation is 4.38. p value of finger toe touch test is 0.04 and t value is 2.07. Inference is significant. The results of this study conclude that traction straight leg raise (TSLR) was effective in improving hamstring tightness in college going students. We also found that compression straight leg raise (CSLR) was equally effective in improving hamstring tightness in the college going students. Therefore we conclude that both the techniques show improvement in hamstring tightness. The Group A and group B showed 12 degrees and 9 degrees improvement respectively for active knee extension test. In the straight leg raise test group A showed 13 degrees and group B 9 degrees improvement. The group A and group B in finger toe touch test showed 9 cm and 5 cm improvement respectively. Therefore, we conclude that both the techniques are equally effective in reducing hamstring tightness.